TWO ALGORITHMS FOR FAREY TREE - Kocić, Ljubiša; Stefanovska, Liljana (Matematichki Bilten, 2005)
The Farey tree is a binary tree containing all rational numbers from \([0, 1]\) in an ordered way. It is constructed hierarchically, level by level, using the Farey mediant sum. Some known algorithms, connected with the Farey tree construction are reviewed and two new algorithms are proposed.